High prevalence of vancomycin non-susceptible and multi-drug resistant enterococci in farmed animals and fresh retail meats in Bangladesh - Samad, M.A.; Sagor, M.S.; Hossain, M.S.; Karim, M.R.; Mahmud, M.A.; Sarker, M.S.; Shownaw, F.A.; Mia, Z.; Card, R.M.; Agunos, A.; Lindahl, Johanna F. (Springer, 2022)
The emergence of antimicrobial resistant Enterococcus spp., a main cause of untreatable nosocomial infection, in food animals and dissemination to humans is a public health risk. The study was performed to determine the prevalence and antimicrobial resistance, and virulence characteristics of Enterococcus faecalis and Enterococcus faecium in food animals and meats in Bangladesh. Enterococcus spp., were confirmed using sodA gene specific PCR, and antimicrobial resistance and virulence properties were characterized by PCR. Enterococcus spp. were recovered from 57% of the collected samples (n = 201/352). Farm samples yielded significantly higher (p ≤ 0.05) prevalence (62%) than that of retail meat samples (41%). E. faecalis (52%) is most frequently isolated species. Greater proportions of isolates exhibited resistance to tetracycline (74%), erythromycin (65%) and ciprofloxacin (34%). Fifty-one isolates are vancomycin non-susceptible enterococci (VNSE), of which forty-seven are MDR and twenty are linezolid resistant, a last line drug for VNSE. Virulence factors such as gelatinase (gelE), aggregation factor (asa1) and sex pheromone (cpd) are detected along with vancomycin resistance gene (vanA, vanB and vanC2/C3) in VNSE isolates. The high prevalence of MDR enterococci in food animals and retail meats may cause consumers infections with concomitant reduction of available therapeutic options.